2013
DOI: 10.1111/cch.12121
|View full text |Cite
|
Sign up to set email alerts
|

Family‐centred music therapy to promote social engagement in young children with severe autism spectrum disorder: a randomized controlled study

Abstract: FCMT improves social interactions in the home and community and the parent-child relationship, but not language skills or general social responsiveness. This study provides preliminary support for the use of FCMT to promote social engagement in children with severe ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 39 publications
5
95
0
4
Order By: Relevance
“…Two recent studies by Thompson, McFerran, and Gold (2014), and by Schwartzberg and Silverman (2016) investigated parents' perception of music therapy with autistic children. Thompson et al (2014) concluded that family-centred music therapy strengthens the parent-child relationship.…”
Section: Parents In Music Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies by Thompson, McFerran, and Gold (2014), and by Schwartzberg and Silverman (2016) investigated parents' perception of music therapy with autistic children. Thompson et al (2014) concluded that family-centred music therapy strengthens the parent-child relationship.…”
Section: Parents In Music Therapymentioning
confidence: 99%
“…Thompson et al (2014) concluded that family-centred music therapy strengthens the parent-child relationship. Parents perceived an improvement in the quality of their child's social interactions as well as in their own abilities to relate positively to the child.…”
Section: Parents In Music Therapymentioning
confidence: 99%
“…After two years, these positive changes were sustained and confirmed as manifested by the child's enhanced social interaction. Two decades since the first MIT intervention, Thompson, et al [37] reveal the same conclusion that supports the contribution of music therapy to social engagement in children with severe ASD.…”
Section: Music Approach Interventionmentioning
confidence: 74%
“…This study employed music as proven effective to address communication [12,25,93], socialization [12,25,36,37,39], motor both in gross and fine [25,58], and maladaptive behavior [20,25,38,39]. Further, play confirmed to be effective in areas of communication which includes verbal expression and language [19,42,44,45], socioemotional [19,41,42] and socialization [42,44,45].…”
Section: Implication Of Pre-test and Post-test Differences For The Prmentioning
confidence: 99%
“…ASD children (especially in developed countries) as a form of psychosocial intervention has been conducted individually, in groups, or involving families (Oldfield, 1993;Thompson, McFerran& Gold, 2014).…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%